2019
DOI: 10.1001/jamanetworkopen.2019.12052
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary vs Electrically Stimulated Activation in Age-Related Muscle Weakness

Abstract: This cross-sectional study compares voluntary neural activation of lower extremity muscles in clinically weak older adults vs stronger older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Previous research has shown that physical decline in the process of aging may be at least partly due to damage to the brain or nerve function, not just disorders of skeletal muscle, and the hippocampus might be involved in the regulation of human body functions ( Bland and Oddie, 2001 ; Clark et al, 2019 ). It is well known that the hippocampus is devoted to balance regulation and sensory motor integration ( Bland and Oddie, 2001 ), while the hippocampus body and anterior cingulate gyrus are involved in memory and executive function ( Mcgough et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that physical decline in the process of aging may be at least partly due to damage to the brain or nerve function, not just disorders of skeletal muscle, and the hippocampus might be involved in the regulation of human body functions ( Bland and Oddie, 2001 ; Clark et al, 2019 ). It is well known that the hippocampus is devoted to balance regulation and sensory motor integration ( Bland and Oddie, 2001 ), while the hippocampus body and anterior cingulate gyrus are involved in memory and executive function ( Mcgough et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…While declines in handgrip strength have been thought to be primarily attributed to agerelated changes in the muscular system, it has also been postulated that decreased handgrip strength is more a product of diminished neural and motor system capacity [15]. For example, during a strength capacity assessment, nervous system deficiencies may limit the amount of muscle force aging adults can generate to about half of what would be expected if the skeletal musculature were fully activated by the nervous system, primarily due to poor neuromuscular activation and motor unit recruitment [16,17]. The dysfunction observed in the neural and motor systems during aging that influence handgrip strength declines may also be linked to the incipient and progressing cognitive impairment [18].…”
mentioning
confidence: 99%
“…However, inferring information about muscle performance from voluntary contractions assumes that descending drive from the central nervous system is optimal 12,13 . While many individuals display high levels of voluntary activation, 14 this is not always the case, particularly in weaker older adults 15,16 and patients examined in clinical settings 17 . Furthermore, assessments of maximal strength during voluntary contractions assume that participants are motivated and compliant with the testing procedures 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Its use provides investigators with a great deal of data. Specifically, by providing supramaximal electrical stimulation to a nerve/muscle group during a maximal effort contraction and at rest, the interpolated twitch technique can be used to parse out various voluntary and involuntary factors that may influence strength measurements 16,20,21 . Isolated measurements of involuntary torque are particularly useful in studying skeletal muscle, given that they are not reliant on voluntary effort, motivation, and central nervous system activity.…”
Section: Introductionmentioning
confidence: 99%